2018
DOI: 10.1071/fp16420
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cytosolic calcium elevation in plants: the role of ion channels, calcium extrusion systems and NADPH oxidase-mediated 'ROS-Ca2+ Hub'

Abstract: Elevation in the cytosolic free calcium is crucial for plant growth, development and adaptation. Calcium influx into plant cells is mediated by Ca2+ depolarisation-activated, hyperpolarisation-activated and voltage-independent Ca2+-permeable channels (DACCs, HACCs and VICCs respectively). These channels are encoded by the following gene families: (1) cyclic nucleotide-gated channels (CNGCs), (2) ionotropic glutamate receptors (GLRs), (3) annexins, (4) ‘mechanosensitive channels of small (MscS) conductance’-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 174 publications
1
85
0
3
Order By: Relevance
“…Their transmembrane topology and structural highlights are summarized in Fig. and Table and were recently comprehensively discussed by Demidchik & Shabala (). The heterologous expression studies (Table ) and in vivo electrophysiological tests (Table ) demonstrated that some of these genes do indeed encode Ca 2+ ‐permeable channels.…”
Section: Physiological and Structural Characteristics Of Plant Ca2+‐pmentioning
confidence: 98%
See 4 more Smart Citations
“…Their transmembrane topology and structural highlights are summarized in Fig. and Table and were recently comprehensively discussed by Demidchik & Shabala (). The heterologous expression studies (Table ) and in vivo electrophysiological tests (Table ) demonstrated that some of these genes do indeed encode Ca 2+ ‐permeable channels.…”
Section: Physiological and Structural Characteristics Of Plant Ca2+‐pmentioning
confidence: 98%
“…Membrane topology of Ca 2+ ‐permeable channel subunits (adapted from Demidchik & Shabala, , with modifications). NT and CT , N‐ and C‐terminal calmodulin‐binding sites (CaMBS), respectively; IQ , ‘isoleucine‐glutamine’ domain, which functions as calmodulin‐binding site; CNBD , cyclic nucleotide‐binding domain; P, pore domain; EF , EF ‐hand motif, which binds Ca 2+ ; ATD , amino terminal domain; LBD , ligand‐binding domain; OSCA 1 transmembrane domain (grey colour) could be a cleavable signal peptide.…”
Section: Physiological and Structural Characteristics Of Plant Ca2+‐pmentioning
confidence: 99%
See 3 more Smart Citations